Control of Cone Worm, Dioryctria abietella Denis and Schiffermueller (Lepidoptera : Pyralidae) in Seed Production Areas of Spruce, Picea smithiana Boiss by Systemic Insecticides - Bhandari, R. S.; Pande, Swati; Joshi, M. C.; Zaidi, S. M. H.; Rawat, J. M. S.; Kumar, Vinod (Indian Forester, 2006)
Control of cone worm Dioryctria abietella Denis and Schiff. Infesting cone and seed of spruce (Picea smithiana) in seed production areas was attempted. The systemic insecticides viz thimet, carbofuran, dimethoate, monocrotophos were applied at the point of drip line application in soil and through tree injection at the base of the trees in Seed Production Area (SPA) at Deoban, Kanasar Range, Chakrata Forest Division (Uttaranchal). Tree injection with monocrotophos 36 EC 100 ml with 20 cm Girth of a tree at Breast Height was found superior than the application of granular pesticides in the soil at the drip line. Tree injection could protect 86.49 per cent, cones from the attack of cone worm.